2015
DOI: 10.1007/s10798-015-9307-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial ability learning through educational robotics

Abstract: Several authors insist on the importance of students' acquisition of spatial abilities and visualization in order to have academic success in areas such as science, technology or engineering. This paper proposes to discuss and analyse the use of educational robotics to develop spatial abilities in 12 year old students. First of all, a course to introduce robotics to 6th grade primary school students was designed. The key intention was to prepare practical and motivating sessions in order to foster the students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 10 publications
0
21
0
1
Order By: Relevance
“…While engaging in robotics activities, the young children expanded their terminology and employed more complex sentence structures to explain robots' behaviors or explain their ideas. Julià and Antolí compared 6th graders who participated in a 10-week robotics course with ones who did not join the course [47]. Their study showed that the participating children developed statistically more advanced spatial abilities than non-participating children.…”
Section: Effects Of Robotics Education On Young Children's Learningmentioning
confidence: 99%
“…While engaging in robotics activities, the young children expanded their terminology and employed more complex sentence structures to explain robots' behaviors or explain their ideas. Julià and Antolí compared 6th graders who participated in a 10-week robotics course with ones who did not join the course [47]. Their study showed that the participating children developed statistically more advanced spatial abilities than non-participating children.…”
Section: Effects Of Robotics Education On Young Children's Learningmentioning
confidence: 99%
“…Julia and Antoli compared 6th graders who participated in a 10-week robotics course with ones who did not join the course [10]. Their study showed that the participating children developed statistically deeper spatial abilities than nonparticipating children.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, the consensus is robotic technologies should not be viewed as ordinary tools but as tools to promote the development of innovative ways to enhance the learning environment. Though few studies exist in which educational leaders' perceptions on the role of ethics and the use of robotics are investigated, in the literature educators tend to agree that robotics learners engage in opportunities that enhance critical thinking skills ( Julià and Antolí, 2016). Additionally, educators note the importance of students' adaptation to a technical inspired society.…”
Section: Literature Review Robotics In Educationmentioning
confidence: 99%